2014
DOI: 10.1093/ndt/gfu049
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of multi-frequency bioimpedance spectroscopy in peritoneal dialysis patients: independent predictor of patient survival

Abstract: Our results also indicated that there was no influence of body mass index (BMI) on the hydration parameter OH/ECW. OH/ECW remained an independent predictor of mortality when the BMI and lean tissue index were included in multivariate model. However, it remains to be determined if correcting the OH status of a patient will lead to improvement in mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(156 citation statements)
references
References 30 publications
4
142
3
Order By: Relevance
“…In addition, the ECW:TBW ratio, which is also a predictor of outcome in PD patients, can be influenced by other factors, such as differences in muscle mass or fat tissue mass between patients (30,32). Notably, the relation between the ECW:TBW ratio and the overhydration index which was used both in the present study and in previous cohorts (1,20) is weak (r = 0.31), suggesting that these parameters partly reflect different entities (6). The discussion on the best normalization procedure for mulltifrequency bioimpedance parameters is not fully closed, given the fact that the overhydration index is also influenced by a certain assumption regarding the hydration of lean tissue and fat mass (32,33).…”
Section: Commentariesmentioning
confidence: 59%
“…In addition, the ECW:TBW ratio, which is also a predictor of outcome in PD patients, can be influenced by other factors, such as differences in muscle mass or fat tissue mass between patients (30,32). Notably, the relation between the ECW:TBW ratio and the overhydration index which was used both in the present study and in previous cohorts (1,20) is weak (r = 0.31), suggesting that these parameters partly reflect different entities (6). The discussion on the best normalization procedure for mulltifrequency bioimpedance parameters is not fully closed, given the fact that the overhydration index is also influenced by a certain assumption regarding the hydration of lean tissue and fat mass (32,33).…”
Section: Commentariesmentioning
confidence: 59%
“…A total of five RCTs (published in six papers 60,61,63,76,77,81 ) and eight non-randomised studies (published in nine papers 30,50,[82][83][84][85][86][87][88] ) were included in the review of clinical effectiveness. There was some question over whether or not the RCTs by Onofriescu et al 81 and Onofriescu et al 60 may be reporting the same trial or outcomes from an overlapping patient population.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The Onofriescu et al 60 study reports more relevant outcomes and is more recent. Similarly, there is a possibility that the non-randomised studies by O'Lone et al 82 and Oei et al 83 may involve an overlapping patient population, as both studies recruited at the same centre in the same time period. The corresponding authors of both studies were contacted for further clarification, but no replies were received.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Low serum albumin is an adverse risk factor in patients on dialysis, although for each serum albumin category, the adverse risk is higher for patients on HD than patients on PD (23). Although hydration status measured using bioelectric impedance is a predictor of survival in patients on PD (24), no intervention studies have been reported to date that use it to guide clinical decision-making.…”
Section: Evaluation Of Overhydration In Pdmentioning
confidence: 99%